2021
DOI: 10.1155/2021/8947304
|View full text |Cite
|
Sign up to set email alerts
|

A Network Pharmacology Approach to Reveal the Underlying Mechanisms of Artemisia annua on the Treatment of Hepatocellular Carcinoma

Abstract: Objective. To investigate the potential active ingredients and underlying mechanisms of Artemisia annua (AA) on the treatment of hepatocellular carcinoma (HCC) based on network pharmacology. Methods. In the present study, we used a network pharmacological method to predict its underlying complex mechanism of treating HCC. First, we obtained relative compounds of AA based on the traditional Chinese medicine systems pharmacology (TCMSP) database and collected potential targets of these compounds by target fishin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Besides, when it is activated by upstream signals, PI3K indirectly regulates cell proliferation and survival by phosphorylation of MTOR protein through signaling pathway cascade (Aoki & Fujishita, 2017). In addition, PI3K is strongly associated with inflammation (Aoki & Fujishita, 2017; Zhang M. M. et al., 2021; Zhang S. et al., 2021; Zhang S. W. et al., 2021). Related studies found that MMP9 could play critical roles in many biological processes, such as reproduction, host defenses, cell proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, when it is activated by upstream signals, PI3K indirectly regulates cell proliferation and survival by phosphorylation of MTOR protein through signaling pathway cascade (Aoki & Fujishita, 2017). In addition, PI3K is strongly associated with inflammation (Aoki & Fujishita, 2017; Zhang M. M. et al., 2021; Zhang S. et al., 2021; Zhang S. W. et al., 2021). Related studies found that MMP9 could play critical roles in many biological processes, such as reproduction, host defenses, cell proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…TNF is a target in TNF signaling pathway and is associated with inflammation (Chattopadhyay et al., 2021). HSP90AA1 is a protein‐coding gene and is overexpressed in colon cancers (Zhang M. M. et al., 2021; Zhang S. et al., 2021; Zhang S. W. et al., 2021). Estrogen promotes nNOS activation via G protein‐coupled ESR1 and increases NO to inhibit colon movement in the estrogen signaling pathway (Li et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, Artemisia annua (Asteraceae) is an alternative source of nutrients for humans and livestock and is found in the northern parts of China [ 3 ]. The stems were also traditionally used in Chinese medicine for preventing malaria and enhancing immunity in patients [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. A. annua also displayed anticancer activities against various tumors in vitro and in vivo, as well as exhibiting significant synergistic effects with several clinical anti-tumor medicines [ 6 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The stems were also traditionally used in Chinese medicine for preventing malaria and enhancing immunity in patients [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. A. annua also displayed anticancer activities against various tumors in vitro and in vivo, as well as exhibiting significant synergistic effects with several clinical anti-tumor medicines [ 6 , 12 ]. Several bioactive compounds have been isolated from A. annua , which include sesquiterpenoids, flavonoids, coumarins, triterpenoids, steroids, phenolics, purines and lipids [ 7 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%